2017
DOI: 10.1007/s11010-017-3119-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel guaiane sesquiterpene derivative, guai-2-en-10α-ol, from Ulva fasciata Delile inhibits EGFR/PI3K/Akt signaling and induces cytotoxicity in triple-negative breast cancer cells

Abstract: A novel guaiane sesquiterpene derivative, guai-2-en-10α-ol, from Ulva fasciata Delile exhibits antimicrobial property. U. fasciata extract was reported to exhibit cytotoxicity against cancer. In the present study, we have studied the anticancer potential of the compound, guai-2-en-10α-ol, from U. fasciata. The compound showed selective cytotoxicity toward triple-negative breast cancer (TNBC) cell line (MDA MB-231) in a dose-dependent manner. In treated cells, the apoptotic hallmarks such as formation of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…These results are in line with an earlier report that demonstrated that the algal halogenated monoterpene mertensene induced similar response with G2/M arrest from HT-29 cells [33]. However, other algal terpenes have been described to induce cell cycle arrest in G1 phase in different types of cell lines [36,37]. Cancer metastasis is a leading cause of death in cancer patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with an earlier report that demonstrated that the algal halogenated monoterpene mertensene induced similar response with G2/M arrest from HT-29 cells [33]. However, other algal terpenes have been described to induce cell cycle arrest in G1 phase in different types of cell lines [36,37]. Cancer metastasis is a leading cause of death in cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the AMT tuberatolide B, isolated from the alga Sargassum macrocarpum [31], has been shown to inhibit the viability of various cancer cell lines, including breast cancer (MDA-MB-231), lung cancer (A549), and colon cancer (HCT116), by inducing apoptotic cell death, and sargachromanol E, from Sargassum siliquastrum, has been reported to induce apoptosis in the colon cancer cell line HL-60 [32]. On the other hand, in the last years a variety of algal terpenoids have been reported to induce apoptosis in several cancer cells, including HT-29 [33], Jurkat leukemic cells [34], melanoma B16F10 cells [35,36], and human TNBC cells [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, fucoxanthinol displayed an anti-proliferative effect against drug-resistant HT-29-derived cells, and inhibited xenograft tumor development in a dose-dependent manner [81]. The guaiane sesquiterpene derivative guai-2-en-10-ol isolated from the green seaweed Ulva fasciata, reduced viability of breast cancer MDA-MB-231 cell line [82]. G. tenuistipitata aqueous extract counteracted the cellular proliferation in H1299 cells.…”
Section: Inhibition Of Cell Proliferationmentioning
confidence: 98%
“…Dieckol from E. cava daily administration (40 mg/kg for 15 weeks) decreased cancer cell proliferation in albino rats via induction of apoptosis [95]. The guaiane sesquiterpene derivative guai-2-en-10-ol from green seaweed Ulva fasciata induced apoptosis in MDA-MB-231 breast cancer cell line via direct interaction with the kinase site of EGFR [82]. The halogenated monoterpene, mertensene from red alga Pterocladiella capillacea induced apoptosis in HT-29 and LS174 via modulation of ERK1/2, Akt, and NF B pathways [78].…”
Section: Induction Of Apoptosismentioning
confidence: 99%